Carmim de cochonilha adsorvido em hidroxissal lamelar de zinco com estabilidade aprimorada para aplicação em produtos cárneos cozidos - Ongaratto, Gabriela Cavalca (2021)
The use of viable and safe alternatives to replace the curing salts responsible for the color and preservation of meat products is a challenge, since consumers are looking for healthier food, but are used to the pink/reddish color that is promoted by the use of these salts, which also have proven harmful effects to health. In this study, layered zinc hydroxide salt (ZHN) was synthesized to immobilize and increase cochineal carmine stability, in order to obtain the hybrid dye (ZHN-carmine) to be applied in cooked meat products. ZHN, cochineal carmine and ZHNcarmine were characterized by X-ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). Subsequently, formulations of mortadella and hams were prepared added cochineal carmine or ZHN-carmine and/or curing salts. The mortadella was packaged in artificial wrap and had its color evaluated for 40 days, and the hams were sliced, packed with or without vacuum and exposed to white fluorescent light (1100 LUX) for 15 days. By XRD and FTIR it was observed that the ZHN-carmine had lamellar structure and bands related to the vibrational modes of cochineal carmine and layered zinc hydroxide salt, respectively. By TGA/DSC, the change in the pattern of thermal behavior between the cochineal carmine dye and the hybrid, shows the existence of interactions between the ZHN and the dye. During storage, mortadella added with ZHN-carmine presented a more stable pink/reddish color than the others, including those added with healing salts, and when ZHN-carmine was treated with ultrasound before use, the pink/reddish color besides being stable it was more intense. For ham, it was possible to discriminate the with or without vacuum-packed ham samples based on the value of a* (intensity of the red color), demonstrating the importance of the vacuum-packed in the stability of the red color. At time 0, the ham formulation added with ZHN-carmine had a more intense red color, evidenced by the higher positive value of a*, which was 69 % higher in relation to the formulation added with cochineal carmine. During storage, the hams (ZHNcarmine) packed with and without vacuum, remained stable in relation to the values of a*, without the loss of red color, while the ham added with cochineal carmine packed without vacuum had a significant reduction of 52.5% of the characteristic red color. ZHN-carmine may be considered an alternative ingredient to curing salts in obtaining the pink/reddish color of cooked meat products.